How Does the Effort Spent to Hold a Door Affect Verbal Thanks and Reciprocal Help? - Fox, Glenn R.; Araujo, Helder Filipe; Metke, Michael J.; Shafer, Chris; Damasio, Antonio (Frontiers in Psychology, 2015)
When someone holds a door for us we often respond with a verbal ``thanks.'' But given such a trivial favor, our feelings can vary considerably depending on how the door is held. Studies have shown that verbal thanking increases in relation to door-holding effort. However, it is unclear how such a favor can lead to verbal thanks in addition to reciprocal help. We examined how holding a door in an effortful or non-effortful manner relates to verbal thanking and reciprocal helping. We measured: (1) whether participants verbally thanked the experimenter, (2) whether they agreed to help another person by taking a survey, and (3) whether they helped pick up objects (pens) that the door-holder subsequently dropped. Participants in the effortful condition were more likely to offer verbal thanks, to help pick up the pens, and to walk a greater distance to pick them up. Participants who thanked the door-holder, however, were not more likely to provide help.